Behavioral intention towards e-government in Malaysia: A structural equation modeling approach - Taiwo, A.A. (IGI Global, 2015)
This study examines an amplified unified theory of acceptance and use of technology (UTAUT) in the context of eGovernment to get a better understanding of users' behaviour towards eGovernment. Two hundred and six respondents (206) participated in the study and the data was analysed using structural equation modelling (SEM). The study revealed that Performance Expectancy, Risk Taking Propensity, Attitude towards Computer and Web Trust dimensions are essential precursor of behavioural intention of Malaysians towards eGovernment. The study further suggests that policy-makers can increase eGovernment usage by creating applications that meets expected demands and needs of the people with provision of trust facilitating environment and security conditioned systems. Â© 2015, IGI Global.